Congenital Cytomegalovirus Infection in Twin Pregnancy - Carvalho, AA (2021)
Cytomegalovirus (CMV) infection is one of the preeminent congenital viral infections, and despite its potential morbidity, uncertainty about its physiopathology, prevention and treatment remains until now. We report a case of a dichorionic and diamniotic twin pregnancy in which only one of the fetus had signs of being affected. The first twin had prenatal diagnosis of intrauterine growth restriction and hyperechogenic bowel, attributable to CMV infection, while there was no evidence of infection of the second one. Prenatal treatment was done with maternal administration of valacyclovir and postnatal treatment of the infected newborn with oral valganciclovir with normal neurodevelopment assessment at 12 months corrected age. In this case, maternal CMV infection was not equally transmitted to both fetuses, suggesting that there may be intrinsic fetal and placental factors influencing both transmission and the clinical features of the infection.